Decision support system for vehicle scheduling - C. Gaindric (Computer Science Journal of Moldova, 1999)
A decision support system (DSS) is described to form schedules of traffic from a central warehouse to a set of consumers by cyclic routes. The system may be used by dispatchers at transportation enterprises. The system structure, short description of modules, and algorithms solving the originating problems are presented.